Impact of Independent Pharmacist Prescribing on the Future of Pharmacy - Jimmy Shangala Mwawaka (University of Minnesota Libraries Publishing, 2016)
Pharmaceutical care as a philosophy is neither universal nor sustainable. Pharmacist prescribing will be the most unifying and transformative innovation in pharmacy practice, globally. Scope expansion supported by prescribing rights for pharmacists will impact pharmacy and other professions: community pharmacy will evolve into an independent profession; and pharmacy and medicine will merge. Important decisions in pharmacy education and practice policy must be made in view of these future changes. Conflict of Interest "We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties".   Type: Commentary